AKSIOLOGI PERPUSTAKAAN SEBAGAI SUMBER BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM IAIN PALOPO - Hasbi, Hasbi; Hasriadi, Hasriadi; Azhari, Nurul Hikmah (Kelola: Journal of Islamic Education Management, 2023)
Many students still need to utilise the library as a learning resource. This study aims to 1) Investigate the library used by students of the Islamic Religious Education (PAI) study program at IAIN Palopo and 2) Analyze the inhibiting factors in using the library as a learning resource. This research is a field research with a qualitative descriptive approach. Data was collected through observation, interviews (with the head of the librarian, staff and students of PAI), and documentation. Data were analysed through data reduction, data presentation, and concluding with triangulation as a form of data validation. The results showed: 1) The use of the library by PAI IAIN Palopo students was low, with visits to the library that were infrequent and mostly occurred while working on assignments or theses. References that students are looking for include hadith, commentary books, and literature related to Islamic religious education. 2) Inhibiting factors include internal factors, such as lack of awareness and motivation of students, as well as external factors, such as the influence of sophisticated technology, which makes students reluctant to use the library, limited time for library services, and un-updated book collections. Increasing student awareness and motivation and increasing support from the lecturers are important to overcome this obstacle. In addition, it is necessary to improve library services, more up-to-date book collections, and strategies to overcome the impact of technology in the context of learning.